New developments in brain metastases - Berghoff, Anna S. (Ther Adv Neurol Disord, 2018)
Patients with brain metastases (BM) are a population of high clinical need for new therapeutic approaches due to, as yet, very impaired survival prognosis. However, only few clinical trials have specifically addressed this prognostically highly heterogeneous patient population. New developments in the treatment of BM patients aim to reduce the side effects of local therapies, for example, by redefining the indications for stereotactic radiosurgery and whole-brain radiotherapy (WBRT) or introducing new applications like hippocampal sparing WBRT. Furthermore, systemic therapies become a more important treatment approach in patients harboring targetable mutations, as recent BM-specific endpoints in several phase III trials have shown promising intracranial efficacy. In addition, immune-checkpoint inhibitors show promising intracranial efficacy, particularly in patients with melanoma and non-small lung cancer BM. Here, we provide a review on the recent new developments in the local and systemic therapy approaches in BM patients.